Living with a hernia: A qualitative study of patient experience of abdominal wall hernias in Ndola, Zambia. (October 2021) - Ljungstrom, Elin; Chibwe, Felix; O'Brien, Catherine; Musowoya, Joseph; Grimes, Caris E
Despite hernias being one of the most common surgical problems in low and middle income countries, very little is known about the impact that having a hernia has on the quality of life of patients in these settings. We performed a pilot study to understand how living with a hernia impacts on the quality of life. Twelve semistructured interviews were performed. A number of themes were identified. These demonstrated the significant impact on physical health, ability to work, psychological health and social relationships. Further work is required to better understand the patient perspective and ensure that hernia operations improve quality of life in these settings.